Business Potency of "Indofishme" as an Alternative to Healthy Instant Noodles Rich in Nutrients: Potensi Usaha “Indofishme” Sebagai Alternatif Mie Instant Sehat Kaya Nutrisi - Fitriana, E; Sumartini; Harahap, KS; Nabila , R; Hutapea, N; Nelas, MH; Saputra , N (Procedia of Social Sciences and Humanities, 2022)
Several previous studies have proven that instant noodle products with various innovations show a fairly good level of panelist acceptance. However, the emergence of additional costs due to fortification of fish and seaweed on Indofishme products which can directly lead to an increase in product prices has not been clearly studied. This study aims to determine the level of business feasibility of instant noodles "Indofishme". The study began with the manufacture of instant noodles (noodles with fortified mackerel fish meal and seaweed). Furthermore, all components of costs related to Indofishme's production operations are recorded as information in analyzing Break-Even Point (BEP) and Benefit per Cost Ratio (B/C ratio). The calculation results show that the BEP cost of the product is 3 packages with a B/C ratio of 1.33. It can be concluded that the "Indofishme" noodle production business is economically feasible to run in terms of BEP and B/C ratio. This study is expected to provide information that "Indofishme" has the potential as a new business in the functional food sector, especially the diversification of processed instant noodle products based on healthy seafood (functional noodles). The business Potential of "Indofishme" as an alternative to healthy instant noodles rich in nutrients.